PEMBUATAN BATAKO DENGAN CAMPURAN FLY ASH DAN STYROFOAM Brick Making with a Mixture of Fly Ash and Styrofoam - Agustina Dyah Setyowati; Zakki .; Achmad .; Erika . (Jurnal Ilmiah Teknik Kimia, 2017)
Environmental pollution caused by industial waste need to be concerned. Fly ash and styrofoam are one of those thing. To reduce amount of industrial waste, fly ash and styrofoam can be transformed into something more useful, such as raw material for brick. Physical and cemical properties of fly ash almost the same as cement, and styrofoam can substitude cement and sand. Research shows that dried a brick in 150oC for an hour can accelerate the process of making a brick, but it can decrease the compressive strength, and the percentage of water adsorption is higher than the control sample (A). in addition of 10% fly sh, the compressive strength obtained is 2.5 MPa, and the highest water adsorption is reached, 20.74%. in addition of 0.1% styrofoam, the value of compressive strength and water adsorption are 2.5 MPa and 15,32%. And in combination of 10% fly ash and 0.1% styrofoam, the value of compressive strength and water adsorption are 1 MPa and 19.18%. result of XRD test shows that in both of the sample (sample A and E1), have the same dominant phase of calcium carbonate (CaCO3) with 103% of intensity at 29.404 angle position.Kata Kunci : Environmental pollution, Brick, Fly Ash, Styrofoam, XRD